2004
DOI: 10.1063/1.1773493
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and theoretical investigation of the nonmodal growth of steady streaks in a flat plate boundary layer

Abstract: International audienceAn experimental and theoretical investigation aimed at describing the nonmodal growth of steady and spanwise periodic streamwise streaks in a flat plate boundary layer is presented. Stable laminar streaks are experimentally generated by means of a spanwise periodic array of small cylindrical roughness elements fixed on the plate. The streamwise evolution of the streaks is measured and it is proved that, except in a small region near the roughness elements, they obey the boundary layer sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
140
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 181 publications
(157 citation statements)
references
References 35 publications
17
140
0
Order By: Relevance
“…Comparison of the results by Fransson et al (2004) with similar experimental studies in the literature showed that the flow may be modulated differently depending on the roughness element configuration. They are all characterized by the formation of streamwise elongated velocity perturbations and differ in the relative position of the high and low speed streaks with respect to the roughness elements.…”
Section: Realizing Drag Reduction By Means Of a Passive Controlmentioning
confidence: 53%
See 3 more Smart Citations
“…Comparison of the results by Fransson et al (2004) with similar experimental studies in the literature showed that the flow may be modulated differently depending on the roughness element configuration. They are all characterized by the formation of streamwise elongated velocity perturbations and differ in the relative position of the high and low speed streaks with respect to the roughness elements.…”
Section: Realizing Drag Reduction By Means Of a Passive Controlmentioning
confidence: 53%
“…This is due to the presence of the wake, which persists downstream forming the low speed streak. Conversely, in the experiments reported in Fransson et al (2004), similarly to what was observed by Bakchinov et al (1995); Kendall (1990), after a complex region of growing and decaying modes a high speed region is induced behind the roughness element. An explanation for this behavior can be found by considering the perturbation induced by a roughness element in a wall-bounded shear flow (Hunt et al, 1978;Acarlar & Smith, 1987;Dèlery, 2001).…”
Section: Realizing Drag Reduction By Means Of a Passive Controlmentioning
confidence: 55%
See 2 more Smart Citations
“…It is also known that streaks can have a stabilizing effect on the small amplitude Tollmien-Schlichting waves that comprise the initial stage of transition in many applications with low levels of external forcing. Moreover it is now realized that the stable laminar streaks generated by surface roughness elements can be used to control transition in these applications (Fransson et al 2004(Fransson et al , 2006. It therefore seems important to understand the physical mechanisms related to the potential disturbance growth in the wake flow behind surface roughness elements.…”
Section: Introductionmentioning
confidence: 99%